Alcohol consumption among university students in Ethiopia: a systematic review and meta-analysis of epidemiological studies - Debela, Sisay Abebe; Tefera, Yonatal Mesfin; Debela, Endashaw Abebe; Gebrehiwot, Mesfin; Bezie, Anmut Endalkachew; Dadi, Ejeta Batu; Daba, Chala (Frontiers in Public Health, 2025)
BackgroundAlcohol consumption among University students in Ethiopia is a pressing public health concern. Many existing studies tend to focus on students across all educational levels, including combinations of high school, college, and University students, and determining substance use behaviors, such as Kchat chewing, cigarette smoking, and alcohol consumption. This approach lacks a comprehensive national perspective, particularly with regard to University students. Notably, there is no research available that assesses the extent of alcohol consumption among university students in Ethiopia on a national level. This systematic review and meta-analysis aim to provide comprehensive insights into the prevalence of alcohol use among University students and the factors influencing their drinking behaviors.MethodsWe conducted a comprehensive electronic search across various international databases and libraries, including PubMed/MEDLINE, Hinari, Science direct, African Journals Online and Google Scholar, to identify relevant published reports. The study strictly adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA) guidelines. Analysis was performed using STATA 14 software, employing a random effects model to estimate the pooled effect with a 95% confidence interval (CI). Heterogeneity was visually assessed using forest plots. Additionally, publication bias was evaluated through funnel plots and Egger’s and Begg’s tests.ResultsWe conducted an analysis of 15 studies involving a total of 10,500 University students in Ethiopia to determine the prevalence of alcohol consumption. Sample sizes across these studies ranged from 188 to 1,239 participants. The pooled prevalence of alcohol consumption was 36.5%. Students who had friend’s currently consuming alcohol were found to be twice as likely to engage in alcohol consumption. Additionally, students in Universities who smoke cigarette were also twice as likely to consume alcohol compared to non-smokers. Furthermore, students with family members who drink alcohol were more likely to consume alcohol compared to those from families without this behavior. The study identified Kchat chewing habit as an additional factor influencing alcohol consumption among University students in Ethiopia.ConclusionAddressing alcohol consumption in these students requires comprehensive interventions that consider these diverse factors to promote responsible drinking and student well-being.